2006
DOI: 10.11606/issn.1678-4456.bjvras.2006.26475
|View full text |Cite
|
Sign up to set email alerts
|

Artérias mesentéricas cranial e caudal em aves (Gallus gallus) da linhagem Cobb 500

Abstract: ResumoEstudaram-se as origens, ramificações e distribuições das artérias mesentéricas cranial e caudal em 30 aves (Gallus gallus) da linhagem Cobb 500, machos, com idade entre 5 e 6 semanas. Os espécimes tiveram seus vasos arteriais preenchidos com solução aquosa corada de Neoprene Látex "450" a 50% e a seguir foram fixados em solução aquosa de formaldeído a 10%. A artéria mesentérica cranial emergiu da face lateral direita da aorta descendente caudalmente à artéria celíaca e através das artérias ileocecal, je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
3

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
2
1
0
3
Order By: Relevance
“…The current investigations revealed that the cranial mesenteric artery was detached from descending aorta caudal to the origin of the celiac artery the same as mentioned by Nickel et al, (1977) and Campos et al (2006) in the fowl and Pinto et al (1998) in the domestic duck. In this connection both celiac and mesenteric arteries arose by common trunk called the celiacomesenteric artery as mentioned by Santos et al (2007) in fish.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current investigations revealed that the cranial mesenteric artery was detached from descending aorta caudal to the origin of the celiac artery the same as mentioned by Nickel et al, (1977) and Campos et al (2006) in the fowl and Pinto et al (1998) in the domestic duck. In this connection both celiac and mesenteric arteries arose by common trunk called the celiacomesenteric artery as mentioned by Santos et al (2007) in fish.…”
Section: Discussionsupporting
confidence: 85%
“…The major arterial branches of the descending aorta, and their supply to the abdominal viscera in the domestic turkey were previously studied by Gadhoke et al (1975).The distribution of the cranial and caudal mesenteric arteries to the intestinal tract was described by Santana et al (2001) and Campos et al (2006) in the fowl, Pinto et al (1998) in the duck.…”
Section: Introductionmentioning
confidence: 96%
“…Após a sua origem, direcionou-se em sentido cranioventral no mesorreto e bifurcou-se em dois ramos, cranial e caudal, em 100% dos animais (Fig. 1A), em concordância com o que foi descrito por NEIRA et al (2016) em avestruz, FARAG et al (2013) em perus, Goldline, MIRANDA et al (2008) em aves Redbro Plumé, CAMPOS et al (2006 em aves Cobb 500, PERES et al (2005) em aves Arbor Acres, CARDOSO et al (2002) em frangos caipiras, SILVA et al (2001) em aves Ross e GETTY (1986).…”
Section: Resultsunclassified
“…2A). A distribuição do referido ramo está de acordo com o que foi descrito em outras linhagens de aves Gallus gallus estudadas por SILVA et al (2010), MIRANDA et al (2009), MIRANDA et al (2008, PERES et al (2005), , CARNEIRO E SILVA et al (2001); em marrecos por CARNEIRO E SILVA et al 2009 No que diz respeito ao número de vasos emitidos pelo ramo caudal da artéria mesentérica caudal, esta percorria o seu trajeto a partir da artéria aorta, e antes de penetrar na parede do reto emitiu ramos que variaram de 1 a 3, os quais se distribuíram para o próprio reto ou cloaca. Do total de aves dissecadas, dezoito apresentaram 1 ramo (60%), dez apresentaram 2 ramos (33,33%) e duas apresentaram 3 ramos (6,67%) (Tabela 3).…”
Section: Resultsunclassified
See 1 more Smart Citation